Patch‐scale culls of an overabundant bird defeated by immediate recolonization. Issue 3 (5th March 2019) - Beggs, Richard; Tulloch, Ayesha I. T.; Pierson, Jennifer; Blanchard, Wade; Crane, Mason; Lindenmayer, David
Abstract: Overabundant native animals cause a variety of human–wildlife conflicts that can require management to reduce their social, environmental, or economic impacts. Culling is an intuitively attractive management response to overabundance, but poor monitoring of results and costs means that evidence for successful outcomes is often lacking. Furthermore, many culls worldwide have been ineffective or counterproductive due to ecological release mechanisms or compensatory responses by the overabundant species. We completed a controlled, replicated, costed, and rigorously monitored experimental cull of the endemic Australian honeyeater, the Noisy Miner ( Manorina melanocephala ). Aggressive exclusion of birds from remnant woodland patches by overabundant Noisy Miners is listed as a Key Threatening Process under Australian conservation legislation due to its impacts on threatened birds. The problem is particularly prevalent in the highly modified agricultural landscapes of eastern Australia. The species impacts avian assemblages at low densities (0.6–0.8 birds/ha) and at a subcontinental scale (>1 million km 2 ). Some ecologists recommend culling as the only management response capable of timely reversal of declines of threatened small woodland birds. We monitored Noisy Miner abundance before and for 12 months after a culling program and found that immediate recolonization from the surrounding landscape negated the impact of the cull. We hypothesize that this is due to a vacuum effect; whereby, birds resident in more marginal habitat around treatment patches move into the vacant territory post‐cull. Modeled mean abundance of Noisy Miners declined by 22% in treatment sites compared to an increase of 4% in control sites in the post‐cull period. Abundance in all sites, however, remained three to five times higher than published ecological impact thresholds. Return on investment analysis indicated no relationship between culling effort and reduction in Noisy Miner abundance. We conclude that culling at a patch scale is not an efficient method of reducing Noisy Miner abundance to levels unlikely to impact threatened woodland birds in the highly modified study landscape, despite estimated costs 18 times lower than another potential management response of revegetation. Our study highlights the importance of building empirical evidence before intuitively attractive but not necessarily ecologically effective management responses are applied more widely.